Locating community impacts of unconventional natural gas across the supply chain: A scoping review. Issue 2 (April 2019) - Buse, Chris G.; Sax, Marieka; Nowak, Nadia; Jackson, Jordan; Fresco, Theresa; Fyfe, Trina; Halseth, Greg
Highlights: Literature on 'upstream' impacts to communities from UNG development is robust and comprised the majority of the articles reviewed. Literature on the 'midstream' and 'downstream' community impacts of UNG are understudied. We identify 28 community impacts across four overarching categories: environmental, infrastructure and social services; socioeconomic; policy and governance. A review of policy mechanisms to reduce risks to communities located across the supply chain is provided. Abstract: Unconventional natural gas (UNG) refers to a suite of technologies that aid in the exploration, extraction, and transportation of natural gas resources. This paper reports on the results of a scoping review examining peer-reviewed articles published between 2009–2018 on the impacts of UNG activities on communities located across the supply chain (i.e. "upstream" communities adjacent to the point of gas extraction, "midstream" communities located near pipelines, and "downstream" communities that are cooling natural gas into liquid form for international export). Our review identified 523 articles, 68% of which focused on the United States. The majority of articles (77%) highlighted community impacts adjacent to the point of extraction, with only 11% and 6% addressing midstream and downstream supply chain impacts. Results classified 28 unique types of community impacts conceptualized within the literature, organized into four categories: environmental impacts; impacts to infrastructure and service delivery; impacts on policy, regulation and participation in decision-making; and socioeconomic impacts. We provide a narrative review to clarify the socioeconomic impacts and possible policy mitigation efforts across the UNG supply chain.